A Statistical quality control project on American Fire Control System Inc. - Cinco, Ronald Allan M.; Patricio, Ramona; Tanlapco, Enrique Paolo (Diliman, Quezon City College of Engineering, 2001)
The industrial quality control course deals with statistical process control, process specifications, and tolerances, acceptance sampling, and life testing products. As a culmination, the researchers conducted a project study on actual manufacturing companies that already had working standards, but needed a (better) system for determining production stability and control. The particular group worked on American Fire Control Systems, Inc. a private corporation specializing in the design and manufacture of fire protection equipment. This industrial setting will help the researchers apply their knowledge of quality beyond the four walls of the classroom, and ultimately would be beneficial to the company under study. American Fire Control Systems, Inc. established its name in the Philippine fire protection industry in 1989, with sprinkler heads as the initial concentration of its business. It maintains the services of Fireguard Manufacturing Corporation in the procurement of the finest raw materials available. The primary aims of this study were to document existing operations, identify improvement opportunities, and offer solutions and recommendations. The researchers' specific objective was to identify the special causes of nonconformities in the sprinkler heads. It was found out that the most apparent defects in the sprinkler heads were deviations in the dimensions. The next step was to identify the causes of these deviations, and the group identified that the biggest of them was that the machine settings and calibrations deviated from their target values overtime. This cause accounted for 28% of nonconformities in the sprinkler heads. Next in line were deviations in tool settings and gauge calibrations and errors in the manual adjustment of machine settings, which represent 24% and 19%, respectively. The other causes are discussed in the remainder of the paper. The study focuses on production and quality control sections. Attention is given to final testing procedures, which is a premium for fire protection equipment such as sprinklers. These products are rarely used, but in the occasion that they are used, they must perform to maximum potential, if not perfectly. Anything less would mean maximum damage to property and even lives. The group interviewed from management personnel all the way to factory floor employees, but much interview time was spent with the plant/quality control manager. On the first visit the group was allowed a plant tour, and from then on the researchers were allowed to roam the factory floor. Visits were also done for the sole purpose of gathering and analyzing historical records. This proved to be a slight problem, for management did not allow the researchers to take the records and forms outside the company premises.
Problems identified were dimensional inconsistencies in seat depths and seat diameters. As of the present there is no scientific basis for the rejection and acceptance of lots sampled, and no statistical method used in determining whether a lot is in control or not. Results of SPC showed that some lots were in control ans some lots were not. The group recommends that the next step to be taken is to design experiments in order to find out which variables contributed to the dimensional inconsistencies. Another quality problem identified was the inadequacy of the existing testing procedures program, and the need for a more comprehensive one. Sampling may be 100% and the end of the manufacturing process, but the in-process sampling needed more statistical backing. SPC results confirmed that some lots were out of control, yet still these lots were accepted. These sprinklers that are not within specifications definitely contributed failures during the testing processes. The process capability was found to be erratic, and the need for a systematic backing-SPC is emphasized by the group. Pareto charts determined which problems occurred the most, and the problems found confirmed that the quality problems tackled by the group were the main causes. Data gathering policies needed to be improved, and the researchers recommend better sampling forms. This complements the preventive maintenance schedule proposed. Finally a system for determining whether the process is in control or not will be in place through the use of SPC. Deviations in seat depths and seat diameters were commonly caused by lack in calibration of both tools and machines, so the company should focus in finding which settings to use in the calibration. Benchmarking, better human resources program, and market research methods were also put forward, to give American Fire Control Systems a more total quality approach. In the analysis of the quality problems and their causes, the group made use of the quality control tools. What proved to be the most helpful were statistical process control charts, the use of these was emphasized. This will benefit the company, which is in need of a system for determining stability and control of the dimensions of its sprinklers. Gauge control procedures are offered by the researchers as solutions to dimension problems. Sampling solutions are also offered in this paper. The details appear in the succeeding pages of this paper.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: American Fire Control System Incorporated; Fire extinction -- Equipment and supplies; Quality control